Working electrode geometry effect: A new concept for fabrication of patterned polymer brushes via SI-seATRP at ambient conditions. (22nd August 2022) - Flejszar, Monika; Ślusarczyk, Kinga; Chmielarz, Paweł; Wolski, Karol; Isse, Abdirisak A.; Gennaro, Armando; Wytrwal-Sarna, Magdalena; Oszajca, Marcin
Abstract: First reports concerning the use of atom transfer radical polymerization (ATRP) to prepare patterned hybrid materials appeared more than 20 years ago. However, the development of new methods of preparation of patterned materials is still at the forefront of scientific interest. In this paper, we describe surface-initiated simplified electrochemically mediated ATRP (SI- se ATRP) under constant current conditions, used for the fabrication of patterned polymer brushes under ambient conditions at the microliter scale. It is shown that appropriate selection of surface and shape of the working electrode (WE) allows handling the polymerization of (meth)acrylates, acrylates and acrylamides directly on the laboratory bench. The complete procedure includes a minimum amount of reagents and an optimal amount of a catalytic complex equal to 300 ppm. The use of a platinum wire mesh electrode guarantees obtaining polymers forming unique patterns. The observed patterning phenomenon could be explained by the mechanism of electrochemically mediated ATRP ( e ATRP) and is directly related to the working electrode geometry, and diffusion of the catalyst Cu I Br/TPMA (where TPMA: tris(2-pyridylmethyl)amine). Graphical abstract: Image 1 Highlights: Diffusion-controlled polymerization for the preparation of hybrid materials. Patterned polymer brushes fabricated via SI- se ATRP at ambient conditions. Two-electrode system applied under constant current conditions for μL-scale ATRP. Dual activator (re)generation during SI- se ATRP of DMAEMA in (in)organic medium. XPS and EDS analysis of patterned polymer brushes.